Sounding the alarm regarding mental health of children and adolescents in relation to parenting style - Nesreen Mosbah Elsayed Mohamed; Fawzia Nabeel Mohammad Abd-Elmageed; Rasha Abdelateef Abdelaziz Ramadan (SpringerOpen, 2024)
Abstract Background Childhood and adolescence are critical periods for physical and mental development. For that, sounding the alarm for the warning signs and red flags of children's mental health disorders is important to promote good health and mental wellness throughout the lifespan. The aim of the study was to assess children's and adolescents' mental health in relation to parenting styles. Methods This study used a descriptive cross-sectional design. From early May 2022 until late October 2022, Zagazig University in Egypt hosted this investigation. Subjects: For this study, 400 parents of Zagazig University staff, employees, and workers who agreed to engage in the current study were gathered as a convenience sample. Tools: In order to get the required data, three tools were utilized. Tool I: A questionnaire for interviews to gather demographic information about the participating parents and their children. Tool II: Adapted Ontario Child Health Study Emotional Behavioural Scale: Parent Version (for children 4-17 years). Tool III: Parenting style scale. Results It was found that criteria for conduct disorder constituted the highest followed by criteria for attention deficit hyperactivity disorder and major depression disorder with a mean and standard deviation of 15.10 ± 3.7, 12.83 ± 3.4, and 11.9 ± 2.8. Also, 66% of the participating parents practiced a permissive parenting style while 18% of them practiced the authoritative style and 16% for the authoritarian style. Conclusion It was determined that criteria of conduct disorder were the most prevalent, followed by criteria of attention deficit hyperactivity disorder and major depressive disorder. Additionally, there was high statistical significance between mental health disorders, parenting styles, and parental educational level. In order to protect children's and adolescents' mental health, this study recommended alerting parents and teachers about red flags and warning signs of mental health disorders for early detection and management. Additionally, educate parents about effective parenting methods and how to behave correctly with their children. Psychological counseling centers for seeking help should be available everywhere and announced.